1992
DOI: 10.1021/ma00032a017
|View full text |Cite
|
Sign up to set email alerts
|

On the observation of a new morphology in poly(arylene ether ether ketone). A further examination of the double endothermic behavior of poly(arylene ether ether ketone)

Abstract: The morphology of solvent-cast or melt-pressed isothermally crystallized poly(ether ether ketone) (PEEK) films was investigated by polarized optical microscropy as a function of crystallization temperature. For crystallization temperatures below 300 °C, only spherulitic morphologies were present whereas, at higher temperatures, a morphological transition from spherulitic to crystal-aggregate-like structures could be observed during isothermal crystallization. As the crystallization temperature is increased, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 4 publications
2
35
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] However, there are many possibilities. Does the P-I crystal melt to be followed with repacking into P-II, which then melts and repacks into P-III?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] However, there are many possibilities. Does the P-I crystal melt to be followed with repacking into P-II, which then melts and repacks into P-III?…”
Section: Resultsmentioning
confidence: 99%
“…Poly(ether ether ketone) (PEEK), [1][2][3][4] poly(1,4-phenyl sulfide) (PPS), 5 syndiotactic polypropylene (sPP), 6 and oligomeric poly(hexamethylene terephthalate) (PHT) 7 have been reported to exhibit multiple endotherms. Poly(aryl ether ketones) and their copolymers are also known to show multiple melting behavior and have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two polymers, PEEK has received more attention thus far, and considerable progress has been made in the understanding of its crystalline structure, [7][8][9][10][11] optical and lamellar morphologies, [12][13][14][15][16][17][18] crystallization kinetics, [19][20][21] and physicochemical properties. 22,23 There are significant differences in the reported results of lamellar structure and lamellar stack dimensions of PEEK.…”
Section: Introductionmentioning
confidence: 99%
“…Similar sheaf-like lamellae have been common in several semicrystalline polymers. Marand et al [20] also reported different birefringences of the spherulites in poly(arylene ether ether ketone) attributable to two types of spherulites. In addition, Lawrence and Shinozaki [21] reported coarse sheaf-like lamellae in non-isothermally treated sPS samples (slow cooling rate at 10 8C/min from the molten state), but finer spherulites (with typical Maltese cross) in sPS samples cooled fast at 200 8C/min from melt.…”
Section: Lamellar/spherulite Morphologymentioning
confidence: 96%